2021
DOI: 10.3390/ma14216439
|View full text |Cite
|
Sign up to set email alerts
|

Time-History Analysis of Composite Materials with Rectangular Microstructure under Shear Actions

Abstract: It has been demonstrated that materials with microstructure, such as particle composites, show a peculiar mechanical behavior when discontinuities and heterogeneities are present. The use of non-local theories to solve this challenge, while preserving memory of the microstructure, particularly of internal length, is a challenging option. In the present work, composite materials made of rectangular rigid blocks and elastic interfaces are studied using a Cosserat formulation. Such materials are subjected to dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Pau and Trovalusci [20] found that the relative rotation is significant in anisotropic materials, whereas it can be negligible in orthotetragonal materials where the internal length trends to vanish. With the advantage of keeping the memory of the microstructure, the Cosserat continuum was used to study many kinds of materials such as layered materials [21,22], fiber-reinforced materials [23,24], granular materials [25], and composites [26][27][28]. Using a homogenization process for the Cosserat continuum, Trovalusci and Masiani [29] numerically and experimentally studied the mechanical behavior of an inclined masonry structure in which microstructures (interfaces) show a different direction from the ordinary masonry structure.…”
Section: Introductionmentioning
confidence: 99%
“…Pau and Trovalusci [20] found that the relative rotation is significant in anisotropic materials, whereas it can be negligible in orthotetragonal materials where the internal length trends to vanish. With the advantage of keeping the memory of the microstructure, the Cosserat continuum was used to study many kinds of materials such as layered materials [21,22], fiber-reinforced materials [23,24], granular materials [25], and composites [26][27][28]. Using a homogenization process for the Cosserat continuum, Trovalusci and Masiani [29] numerically and experimentally studied the mechanical behavior of an inclined masonry structure in which microstructures (interfaces) show a different direction from the ordinary masonry structure.…”
Section: Introductionmentioning
confidence: 99%
“…There are also many examples in which materials with voids [38][39][40] have been studied referring to Cosserat theory, such as foams [41][42][43][44], granular and geo-materials [45][46][47][48][49][50][51], cellular solids [52][53][54] and different kind of structures such as rods [55] and shells [56][57][58] or even multifield models with affine microstructure [5,7]. In order to extend the numerical investigations about the microstructured composite materials made of rigid particles and elastic thin interfaces [59][60][61], the goal is to test the efficiency of the homogenization technique adopted [62,63], to describe porous materials, not yet analyzed with this approach by the authors themselves [64][65][66]. The study is conducted both in static and dynamic conditions, varying the internal characteristics and then proposing a comparison between a discrete model and two continuous models, one micropolar and one classic.…”
Section: Introductionmentioning
confidence: 99%